The epidemiology of kuru in the period 1987 to 1995 - Alpers, Michael (Commonwealth Department of Health and Ageing, 2005)
In the 9-year period 1987 to 1995 there were 66 deaths from kuru, 17 males and 49 females. The number of deaths per year ranged from 3 to 12. All deaths occurred south of a line drawn through the centre of the kuru region perpendicular to the axis of social change. The mean age at death was 49 years, with a gradual increase in this age with time. The last patient aged in their 20s died in 1987 and the last in their 30s died in 1991. The period shows a waning epidemic, with dramatically fewer deaths than in the early years of epidemiological surveillance 30 years before. Nevertheless, the clinical features and duration of the disease were unchanged. Transmission of kuru stopped by 1960 and patients seen in the period 1987-1995 showed long incubation periods, which in 1995 would have been at least 35 years. The proportion of males was much higher than in the early years; because males were effectively exposed only in childhood their incubation periods were in many cases likely to be over 50 years. The work of the Kuru Surveillance Team in maintaining a rigorous surveillance of kuru epidemiology over this period is described.